Strategic positioning of e-commerce business models in the portfolio of corporate banking - Frank Stehling; Jürgen Moormann (Hochschule für Bankwirtschaft (HfB), 2001)
The emergence of e-commerce leads to a fundamental change for the financial industry. The transition into a digital economy produces numerous new opportunities as well as great risks. B2B e-commerce in particular is considered a promising field for the future. As B2B is very closely related to corporate banking, emerging B2B e-commerce business models should constantly be evaluated to see how they fit into the portfolio of current corporate banking activities. This paper provides a framework for a systematic examination of B2B ecommerce business models and their position in the portfolio of corporate banking. The framework is based on recent work on roles and tasks in business networks. The evaluation of 17 selected business models has been performed by a two-stepapproach which includes interviews with experts and a specific scoring model. The paper indicates that certain business models, like e-marketplaces, seem to be less attractive despite of huge investments of German banks in this field. However, models combining a bank's core competence with new technology offer a high potential in e-commerce activities.
urn:nbn:de:101:1-2008071673
Keywords: 330